2012
DOI: 10.1002/pen.23137
|View full text |Cite
|
Sign up to set email alerts
|

Physical aging and thermal aging resistance of polycarbonate/poly(styrene‐b‐(ethylene‐co‐butylene)‐b‐styrene) blends

Abstract: The effect of thermal annealing on the mechanical properties of polycarbonate (PC) was investigated by tensile testing, Izod impact testing, and differential scanning calorimetry (DSC). An endothermic peak appeared in the DSC curve by annealing at various temperatures below T g . The peak area, as a measure of the degree of physical aging, increased with annealing time. The Izod impact strength decreased suddenly just before an endothermic peak became detectable. The results imply that at the very early stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…It is well known that the relaxation during annealing leads the system toward equilibrium, which is commonly denoted as an enthalpy relaxation. The regularization of macromolecular chains should make the system harder, 64 which is apparently opposite to our results. Takahara et al mentioned that there were density fluctuations at first followed by a decrease in density in the low density regions during the annealing process for PMMA, which may result in the improvement of local mobility of macromolecular chains.…”
Section: Glass Transition Temperatures (T G ) Measured Using Mdsccontrasting
confidence: 99%
“…It is well known that the relaxation during annealing leads the system toward equilibrium, which is commonly denoted as an enthalpy relaxation. The regularization of macromolecular chains should make the system harder, 64 which is apparently opposite to our results. Takahara et al mentioned that there were density fluctuations at first followed by a decrease in density in the low density regions during the annealing process for PMMA, which may result in the improvement of local mobility of macromolecular chains.…”
Section: Glass Transition Temperatures (T G ) Measured Using Mdsccontrasting
confidence: 99%
“…For example, polycarbonate has been found to lose its toughness when aged at temperatures below T g . This has been recently confirmed by Suzuki et al (2012) who showed that the Izod impact strength decreased suddenly in the very early stage of physical aging and suggested that annealing may trigger a ductile-to-brittle transition in BPAPC.…”
Section: Phase-separated Blendssupporting
confidence: 52%
“…More recent studies have shown that when blending BPAPC with a hydrogenated styrene-butadiene-styrene block copolymer (SEBS), aging of the polycarbonate component proceeded at the same rate as in the pure polymer, but the Izod impact strength did not decrease. This thermal aging resistance was attributed to the negative pressure effect of the SEBS particles leading to enhanced local segment dynamics of BPAPC (Suzuki et al 2012).…”
Section: Phase-separated Blendsmentioning
confidence: 96%
“…We observe that t a * is strongly dependent on the volume fraction of the rubbery domain, which is consistent with other reports of physical aging of rubber-toughened materials. 18,67,68 Although this trend is a function of composition, the suppression of embrittlement may also be due to the morphology of the BCPs. Wu previously reported that shear yielding was more favorable for rubber-toughened systems with shorter interparticle distances.…”
Section: Resultsmentioning
confidence: 99%